Balancing cultural shock and economic development: A study of impacts on local culture in the Mandalika Special Economic Zone - Dede Suleman; Supiandi Supiandi; Sri Budi Cantika Yuli; Zaenal Muttaqin; Uwi Martayadi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to investigate the dual impacts of cultural shock and economic development in the Mandalika Special Economic Zone on the preservation of local culture. Method — Employing a qualitative approach, this research utilizes in-depth interviews and observations to collect data from residents, tourists, and stakeholders within the Mandalika. The gathered insights provide a comprehensive understanding of the cultural impacts, economic developments, and changes in behavior, lifestyle, and cultural norms.Result — The study reveals a range of positive and negative impacts stemming from the collision of local culture with global influences. Positive effects include the introduction of local culture to the world, economic empowerment through tourism, preservation through education, and increased cultural awareness. Conversely, negative outcomes encompass cultural dilution, excessive commercialization, clashes of values, social imbalances, and shifts in lifestyle. These changes manifest in increased social interactions, adoption of global business ethics, modern lifestyle adoption, shifts in consumption patterns, adjustments to tourist expectations, clothing influences, and more.Contribution — This research contributes to the understanding of the intricate interplay between cultural shock, economic growth, and the preservation of local culture in SEZs. By delineating the positive and negative outcomes, this study informs stakeholders and policymakers about the challenges and opportunities presented by cultural shock. It underscores the necessity for balanced strategies that uphold cultural heritage while harnessing economic benefits in the context of SEZ development.